2021
DOI: 10.3389/fimmu.2021.625993
|View full text |Cite
|
Sign up to set email alerts
|

Induced Transient Immune Tolerance in Ticks and Vertebrate Host: A Keystone of Tick-Borne Diseases?

Abstract: Ticks and tick transmitted infectious agents are increasing global public health threats due to increasing abundance, expanding geographic ranges of vectors and pathogens, and emerging tick-borne infectious agents. Greater understanding of tick, host, and pathogen interactions will contribute to development of novel tick control and disease prevention strategies. Tick-borne pathogens adapt in multiple ways to very different tick and vertebrate host environments and defenses. Ticks effectively pharmacomodulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 318 publications
(423 reference statements)
0
34
0
Order By: Relevance
“…There is a lack of direct experimental evidence addressing the potential for repeated tick infestations in inducing transient immune tolerance in natural or reservoir hosts [131,132]. Studies suggest that T cells collected from BALB/c mice previously infested with I. ricinus exhibit a suppressed response to in vitro concanavalin A stimulation, compared to cells from non-infested mice [133].…”
Section: Immune Tolerancementioning
confidence: 99%
“…There is a lack of direct experimental evidence addressing the potential for repeated tick infestations in inducing transient immune tolerance in natural or reservoir hosts [131,132]. Studies suggest that T cells collected from BALB/c mice previously infested with I. ricinus exhibit a suppressed response to in vitro concanavalin A stimulation, compared to cells from non-infested mice [133].…”
Section: Immune Tolerancementioning
confidence: 99%
“…The early observations in bovine acquired resistance and confirmation in laboratory trials and human biopsy studies showed an integral role of histamine and basophils in a successful resistance response against tick infestations. Ticks’ ability to modulate host itch, hemostasis, and immune responses is impressive, redundant, and most evident during an initial infestation for those species that develop and express acquired resistance [ 28 , 48 , 63 , 112 , 113 , 114 , 115 , 116 , 117 ]. Thus, ticks engorge readily, fully, and elicit little cutaneous irritation and inflammation during an initial infestation of species that are capable of developing acquired resistance [ 57 , 118 ].…”
Section: Common Elements Of Host Responses Leading To Acquired Resistancementioning
confidence: 99%
“…Thus, ticks engorge readily, fully, and elicit little cutaneous irritation and inflammation during an initial infestation of species that are capable of developing acquired resistance [ 57 , 118 ]. However, the initial infestation stimulates the development of immune effectors that counteract actions of tick saliva components so that during subsequent infestations the actions of tick modulators of host defenses are diminished and the multiple elements of acquired resistance are expressed [ 28 , 57 , 63 , 107 , 112 , 113 , 114 , 117 , 118 , 119 , 120 , 121 ].…”
Section: Common Elements Of Host Responses Leading To Acquired Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…They have an ability in efficiently taking a blood meal through biting host and allowing viral survival and replication within them for an extensive period of time [20][21][22][23] . Ixodid ticks are reported to be the most prominent vectors that play key role(s) in the flavivirus acquisition and transmission cycle 20 .…”
Section: Introductionmentioning
confidence: 99%